An approximate method for solving assignment problem - Marko, M.Y.; Tsegelik, H.H. (Математичне моделювання в економіці, 2017)
This paper presents an approximate method for solving assignment problem that makes it possible to assign tasks to agents in order to gain utmost overall efficiency in completing all the tasks. An example is provided for algorithm illustration.